IMPLICATIONS OF THEOLOGICAL THINKING CHARACTERISTICS OF 21ST CENTURY PALEMBANG SCHOLARS FOR ISLAMIC EDUCATION - Nasution, Nurseri Hasnah (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2024)
This study aims to analyse the implications of the characteristics of theological thought of Palembang scholars on Islamic education in Palembang city. This issue is important to discuss to see the transmission and transformation of the scholars' knowledge in building the consistency of Islamic theology teaching. This research is a qualitative research with a phenomenological approach. The data were obtained from relevant documentation sources and in-depth interviews. Data analysis uses the flow of Miles Huberman analysis stages. This research succeeded in finding academic facts that the 21st century Palembang scholars have theological views characterised by Asy'ariyyah theology. The character of Asy'ariyah theological thought internalised by Palembang scholars is able to maintain the transmission of theological knowledge and ensure the continuity of tradition and civilisation in Palembang City. The contextualisation of theological thought of the Palembang scholars has an impact on Islamic education institutions in Palembang.